Kajian Yuridis Permenkumham Nomor 10 Tahun 2020 Sebagai Upaya Pencegahan Covid-19 - Helda Rahmasari; Stevri Iskandar; Lidia Br Karo (Universitas Batanghari Jambi, 2022)
Assimilation is the process of fostering prisoners and children carried out by blending prisoners and children in community life, this is regulated in Article 1 number 4 of the Regulation of the Minister of Law and Human Rights Number 03 of 2018. The focus of this research is on assimilation given to children. To break the chain of spread of Covid-19, the Minister of Law and Human Rights has also issued Minister of Law and Human Rights Regulation Number 10 of 2020 concerning Conditions for Providing Assimilation and Integration Rights for Prisoners and Children in the Context of Prevention and Control of the Spread of Covid-19 which was promulgated in dated March 30, 2020. The research approach uses normative legal research because it is carried out by researching library materials or secondary data in this case researching and analysing Minister of Law and Human Rights Regulation Number 10 of 2020 through a statutory approach, conceptual approach and philosophical approach by collecting data through document studies and qualitative analysis. The results of the study indicate that assimilation in the Covid-19 pandemic is not an appropriate policy, this is based on unstable social and economic conditions to support the implementation of this. Because as long as prisoners are still state-guided citizens, it should be the state's obligation to fulfilling the prisoners' rights as regulated in Article 14 of Law Number 12 of 1995.